Long Chain Effects on DNA‐Binding and Cytotoxicity to Cancer Cells in Metallo‐Supramolecular Oligomers. Issue 26 (9th July 2018) - Rana, Utpal; Hossain, Md. Delwar; Chakraborty, Chanchal; Nagano, Reiko; Morita, Hiromi; Hattori, Shinya; Minowa, Takashi; Higuchi, Masayoshi
Abstract: We synthesized Fe(II)‐based metallo‐supramolecular oligomers with the different degree of polymerization (DP) (DP‐1, −5 and −10) by changing the molar ratio of Fe(II) acetate and bis(terpyridyl)benzene to 1:2, 5:6, and 10:11, respectively. We investigated the chain length effects on the binding affinity to DNA and cytotoxicity to cancer cells in the oligomers. DP‐10 showed five‐time larger DNA binding constant and four‐time stronger cytotoxicity than DP‐1. We also studied the cell apoptosis assay using annexin V‐FITC/PI staining by flow cytometry and revealed that the ratio of early and late apoptosis cells increased from 15.6% (DP‐1) to 61.4% (DP‐10) with increasing the chain length. Abstract : Different chain length metallo‐supramolecular oligomers were synthesized by changing the molar ratio of the metal and ligand. Chain length effect of oligomers on DNA‐binding and cytotoxicity to cancer cell were revealed. The binding affinity to DNA and cytotoxicity to cancer cells were enhanced with chain length. Large chain length oligomer showed five‐times more DNA binding activity and higher cytotoxicity than small‐one.